What Is the Effect of High-dose Radiation on Bone in Patients With Sacral Chordoma? A CT Study. Issue 3 (March 2018) - van Wulfften Palthe, Olivier; Jee, Kyung-Wook; Bramer, Jos A. M.; Hornicek, Francis J.; Chen, Yen-Lin E.; Schwab, Joseph H.
Abstract: Background: Effects of high-dose radiation using protons and photons on bone are relatively unexplored, but high rates of insufficiency fractures are reported, and the causes of this are incompletely understood. Imaging studies with pre- and postradiation scans can help one understand the effect of radiation on bone. Questions/purposes: The purpose of this study was to assess the effects of high-dose radiation on the trabecular density of bone in the sacrum using CT-derived Hounsfield units (HU). Methods: Between 2009 and 2015, we treated 57 patients (older then 18 years) with sacral chordoma. Fourteen (25%) of them were treated with radiation only. The general indication for this approach is inoperability resulting from tumor size. Forty-two (74%) patients were treated with transverse sacral resections and high-dose radiotherapy (using either protons or photons or a combination) before surgery and after surgery. During this time period, our indication for this approach generally was symptomatic sacral chordoma in which resection would prevent further growth and reasonable sacrifice of nerve roots was possible. Of those patients, 21 (50%) had CT scans both before and after radiation treatment. We used HU as a surrogate for bone density. CT uses HU to derive information on tissue and bone quantity. A recent study presented reference HU values for normal (mean 133 ± 38 HU), osteoporotic (101 ± 25 HU), and osteopenic bone (79 ± 32 HU). To adjust for scanning protocol-induced changes in HU, we calculated the ratio between bone inside and outside the radiation field rather than using absolute values. To assess the effect of radiation, we tested whether there was a difference in ratio (sacrum/L1) before and after radiation. A control measurement was performed (L2/L1) and also tested for a difference before and after radiation. Statistical analyses were performed using the paired t-test. Results: The effects of radiation appeared confined to the intended field, because the bone density outside the treated field was not observed to decrease. The ratio of HU (a surrogate for bone density) in L2 relative to L1 did not change after radiotherapy (preradiation mean: 0.979 ± 0.009, postradiation mean: 0.980 ± 0.009, mean difference outside the radiation field: -0.001, 95% confidence interval [CI], -0.009 to 0.007, p = 0.799). The ratio of HU within the radiation field relative to L1 decreased after radiotherapy (preradiation mean: 0.895 ± 0.050, postradiation mean: 0.658 ± 0.050, mean difference inside the radiation field: 0.237, 95% CI, 0.187-0.287, p < 0.001), suggesting the bone density stayed the same outside the radiation field but decreased inside the radiation field. Conclusions: Trabecular bone density decreased after high-dose radiation therapy in a small group of patients with sacral chordoma. High-dose radiation is increasingly gaining acceptance for treating sacral malignancies; further long-term prospective studies using calibrated CT scanners and preferably bone biopsies are needed. Level of Evidence: Level IV, therapeutic study.